Tendencies in the synoptic resurrection tradition - Schnell, C. (Neotestamentica, 1989)
Although many exegetes assume that the synoptic tradition was transmitted according to certain tendencies or laws of oral transmission, they do not spend much time verifying this assumption. This essay investigates the way in which tendencies are used by various scholars (Bultmann, Craig, Paulsen, and Crossan) to establish the oldest or most reliable witness to the resurrection of Jesus Christ. It is concluded that an analysis of the resurrection traditions in terms of tendencies does not yield much in the way of positive results.